2022
DOI: 10.21203/rs.3.rs-1943704/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The journey to a Learning Health System in primary care: a qualitative case study utilising an embedded research approach

Abstract: Background Healthcare systems may be resilient and adaptive, but they are not fit for purpose in their current state. Increasing threats to health system sustainability have underscored the need to move towards a learning health system in which research and data are used routinely in clinical practice to facilitate system improvement. This study aimed to evaluate a university-based general practice to establish which elements of the learning health system were being realised within the practice and determine … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…We have initiated a programme of work in Australia investigating how the concept of an LHS may be applied in our unique primary health system, with applications to other primary care systems including those in Britain. 15 Our recent case study, modelling a university-based general…”
Section: Learning Health Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have initiated a programme of work in Australia investigating how the concept of an LHS may be applied in our unique primary health system, with applications to other primary care systems including those in Britain. 15 Our recent case study, modelling a university-based general…”
Section: Learning Health Systemsmentioning
confidence: 99%
“…practice in Sydney against LHS principles, has indicated that the practice is operating across several dimensions of the LHS framework, and that staff are willing to embrace additional elements of an LHS. 15 Practical examples of how the domains of an LHS are implemented at the practice-level are also provided, which serve as useful references for practices operating in different contexts. The study also shows overlap between the dimensions of the LHS framework and the quadruple aim framework, 16 which is often used as a key measure for health system performance.…”
Section: High-performing Primary Carementioning
confidence: 99%